Surge protection for sensitive equipment / Wan Izibdin Aladin - Aladin, Wan Izibdin (2000)
This paper presents the surge protection for so-called sensitive equipment. The scope involved the testing of Metal Oxide Varistor (MOV) and diode suppressor to investigate the device reliability clamping action by injecting a high voltage impulse from Heafely Surge Tester. Beside that, an impulse voltage generator was developed to emulate the small-scale voltage spike that could be detected in normal computers and telephone line. The design had achieved 126.4V negative impulse with 2|is rise time. This signal had been used to test the capability of MOV.